Four Decades of Pop-up Book Media in Education: A Bibliometric Analysis - Supriani, Ni Made; Lasmawan, I Wayan; Kertih, I Wayan (Universitas Tanjungpura, 2024)
This study aims to analyse the development and impact of pop-up book media in education over the past four decades, focusing on their effectiveness as pedagogical tools for enhancing learning experiences among young readers. A bibliometric analysis was conducted using data sourced from Scopus, examining 117 articles related to pop-up books and education. The analysis employed performance assessment and science mapping techniques to evaluate research contributions and relationships within the field. The findings reveal that pop-up books engage young readers through interactive, tactile, visual, and textual modalities, significantly improving reading literacy and comprehension. They have been effectively integrated into various subjects, including language and art, and have shown positive outcomes in enhancing creativity and cognitive abilities among children. However, challenges such as high production costs and limited accessibility remain. The study underscores the potential of pop-up books as effective educational resources, advocating for their broader implementation in early childhood education. It suggests that educators and curriculum developers should consider incorporating pop-up books to foster engagement and improve learning outcomes. This research contributes to the existing literature by providing a comprehensive bibliometric overview of pop-up books in education, highlighting their evolving role and the need for further exploration of hybrid learning tools that combine physical and digital elements.